Meta-Analysis: Association of Obesity with Incidence of Polycystic Ovarian Syndrome (PCOS) - Tuminah Tuminah; Cusmarih Cusmarih (Global Health Science Group, 2023)
Polycystic Ovary Syndrome (PCOS) is one of the disorders that often attacks women that cause difficulty obtaining pregnancy. PCOS causes 5-10% of women of reproductive age to become infertile. In Indonesia itself, the exact incidence of PCOS is unknown. Most people with Polycystic Ovary Syndrome (PCOS) do not know that they have the syndrome. This cannot be separated from precipitating factors, one of which is obesity or high body mass index. The purpose of this meta-analysis was to estimate the strength of the effect of obesity on the incidence of PCOS. This study is a systematic review and meta-analysis. Primary data is retrieved through the electronic databases PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords